Abdominal wall-lifting versus CO(2) pneumoperitoneum in laparoscopy: a review and meta-analysis - Ren, Hao (e-Century Publishing Corporation, 2014)
The aim of this study is to compare the operative parameters and outcomes of conventional CO(2)-pneumoperitoneum (PP) versus gasless abdominal wall-lifting (AWL) for laparoscopic surgery. The literature databases of PubMed, Google Scholar and Cochrane Library were searched for randomized controlled trials (RCTs) that had compared the CO(2)-PP approach with that of gasless AWL for laparoscopic surgery and which had been published between 1995 and 2012. Data for the operative parameters (i.e. surgery duration, intraoperative heart rate (HR), perioperative complications, and postoperative duration of hospital stay and time to activity) and outcomes (postoperative shoulder pain, nausea/vomiting (PONV), partial pressure of CO(2) in the blood (PaCO(2)), blood pH, and serum levels of the inflammatory cytokine interleukin (IL)-6) were extracted from the identified RCTs. RevMan software, version 5.2, was used for data synthesis and statistical analysis. Nineteen RCTs were selected for the meta-analysis, involving a total of 791 patients who had undergone laparoscopic operations with CO(2)-PP (n = 399) or gasless AWL (n = 392). Sub-group analysis indicated that the patients who underwent gasless AWL had significantly shorter postoperative time to activity (weighted mean difference (WMD) = -0.23 d, 95% confidence interval (CI): -0.37 to -0.09; P = 0.001), lower incidence of PONV (odds ratio (OR) = 0.24, 95% CI: 0.10 to 0.57; P = 0.001) and lower postoperative PaCO(2) level (WMD = -3.09 mmHg, 95% CI: -4.66 to -1.53; P = 0.0001), compared to the patients who underwent CO(2)-PP. However, the CO(2)-PP method was associated with a significantly shorter surgery duration than the gasless AWL method (WMD = 8.61, 95% CI: 3.19 to 14.03; P = 0.002). There were no significant advantages detected for either approach with respect to the intraoperative HR, the perioperative complication rate, or the postoperative parameters of duration of hospital stay, shoulder pain, blood pH, or serum IL-6 level. We concluded form present study that the gasless AWL method has the features of shorter time, lower postoperative PaCO(2), and lower PONV incidence while the CO(2)-PP method for laparoscopy requires shorter surgical time.